Understanding COVID-19 pandemic related effects on secondary mathematics teachers’ perception of their professional identity - Sheeran, Denis W. (Kansas State University, 2023)
In March, 2020 the Covid-19 pandemic resulted in nationwide school closures and a sudden, unexpected transition to remote teaching and learning for teachers and students across the US. These changes permeated the teaching experience during the 2020-21 school year. Educators in different areas of the country returned either to fully virtual learning environments, various versions of a hybrid school model and, in some cases, fully in-person schooling. In New Jersey, school districts were given the freedom to design virtual or hybrid teaching and learning environments for the 2020-21 school year, deciding on which modality and structure would best fit their community. The purpose of this study is to investigate how secondary mathematics teachers feel about their experiences as teachers in a virtual or hybrid classroom during the Covid-19 pandemic and to explore the effects of the pandemic on the meaning and manifestation of their ongoing professional identity. This study is guided by the theoretical framework principles of phenomenology. This qualitative interpretive phenomenological study was used to describe an event or phenomenon and the lived experiences of the participants in that event, in this case, the lived experiences of secondary mathematics teachers during the Covid-19 pandemic. Semi-structured interviews were conducted with seven secondary mathematics teachers from New Jersey and interpretive phenomenological analysis was performed. The findings show that despite initial feelings of confusion, uncertainty and inadequacy, participants felt that the experience of teaching remotely through the Covid-19 pandemic improved their teaching and brought to light aspects of their personality, instruction, and capabilities that they would choose to continue to foster, or in some cases, eliminate. Participants ultimately did demonstrate a change to their professional identity, pointing toward growth as nurturing teachers, empathetic to student needs, and as practitioners able to acclimate to change and adopt new methodologies and technologies for teaching. The study informs professional development and leadership within schools to the means whereby teachers navigate sudden or extreme change, and leaves room for further study in other content areas or grade bands.
Keywords: Mathematics education; Teacher identity; Educational technology; Covid-19; Pandemic school closures; Pandemic teaching